Single injection, ultrasound-guided planar nerve blocks: An essential skill for any clinician caring for patients with rib fractures. (October 2022) - Schultz, Cody; Yang, Elaine; Mantuani, Daniel; Miraflor, Emily; Victorino, Gregory; Nagdev, Arun
Abstract: In patients with acute rib fractures, regional anesthesia has the potential to reduce suffering, decrease opiate use, lower rates of in-hospital delirium, and improve pulmonary function. While many regional anesthesia techniques are complex and time consuming, two single injection nerve blocks, the serratus anterior plane block and erector spinae plane block, are particularly fast, safe, and simple methods to anesthetize the chest wall. Herein we describe two cases in which the serratus anterior plane block and erector spinae plane block were each used with great success in achieving improved pain control in trauma patients with multiple rib fractures. We believe that any provider who routinely cares for patients with rib fractures (emergency physicians and trauma surgeons alike) can and should learn to use these straightforward nerve blocks.